Frenectomy Using Diode Lasers: A Case Report - Nauman Khan, Amna; Khan, Nauman Rauf; Butt, Hira; Imran, Fatimah; Fatima, Syeda Maryam; Amer, Laiba (Journal of Gandhara Medical and Dental Science, 2023)
OBJECTIVES Lasers are used in almost every aspect of dentistry, be it surgeries, restorations, periodontal procedures, and even aesthetic dentistry. One certain area that requires extra emphasis and importance is the laser-assisted frenectomy. Frenectomy, as the name suggests, is the excision of frenum attachment to the underlying bone. Frenectomy is carried out in the mandible as well as the maxilla. This is a case of a patient undergoing orthodontic treatment who also required a frenectomy, and to minimize the postoperative pain and swelling, the procedure was carried out using a diode laser rather than the conventional surgical procedure.